The Improvement of Elderly Health through the Utilization of Posyandu at Rumberu Public Health Center - Paunno, Magdalena; Djurumana, Yohana; Titarsole, Clara (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Elderly individuals are characterized by a decline in biological functions, which can manifest through physical symptoms, including reduced cognitive abilities. Therefore, accessible healthcare facilities are essential to provide routine health examinations for older adults. The utilization of the Elderly Posyandu (Integrated Health Post) at Rumberu Public Health Center remains notably low, influenced by various factors. The aim of this community service activity was to provide education and guidance on the importance of the Elderly Posyandu and its utilization at Rumberu Public Health Center. The findings indicate that many elderly individuals have not yet accessed the Elderly Posyandu, and available facilities remain limited. Strengthened collaboration among health cadres and the provision of adequate facilities are expected to enhance the utilization of Elderly Posyandu services at Rumberu Public Health Center.